Validitas Buku Siswa IPA Terpadu Dengan Tema Indera Penglihatan dan Alat Optik Menggunakan Model Terpadu Tipe Connected Terintegrasi Pembelajaran Abad 21 - Weri, Firda; Fitriani, Dewi; Irfan, Muhammad Khidayatullah; Obina, Wilfrida Mayasti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the validity of the integrated natural science student book that carries the theme sense of sight and optical devices using connected model integrated 21st century learning, and implemented in Junior High Schools in Kerinci Regency. The research approach used is the Research and Development (R&D) method, referring to the Plomp development model. The instrument used in this study was a validation questionnaire, which had previously gone through a validation process by five experts (validators). The data collection technique was carried out by distributing the questionnaire. The collected data were analyzed descriptively qualitatively through assessment and percentage. The results of the validation analysis of the integrated science student book with the theme sense of sight and optical devices using connected model integrated 21st century learning had an average value of 0.89, this indicates that the book developed is valid and can be used or tested in the learning process